EVENT MANAGEMENT ECONOMIC'S CARE DAY AT SDN 114/VI BANGKO VII, MERANGIN, JAMBI - Mardalena, Mardalena (Dinasti International Journal of Management Science, 2019)
This research aims to explore event management students as the Event Organizer (EO) on event entitled Economic's Care Day (EcoCD) in one of the partner school i.e. SDN 114/VI Bangko VII, Merangin Jambi, Indonesia. The research was conducted using qualitative approach through the method of the analysis of the Constant Comparative Method advanced by Glaser & Strauss. Research on object management event in Economic's Care Day (EcoCD) implemented by the students as the EO independently. The subject of research as well as EO is the entire Economy education study program students in STKIP YPM totally 73 people. All students that have graduated the courses certainly the introduction of management. Research data obtained through several instruments, namely; participant observation, interviews and review of documentation. Based on the results of data analysis confirmed that the ability of management student belongs to is quite good. This can be proved not only by the successful holding of the event in accordance with the planning, but very high enthusiasm of the participants of the event that follows a whole series of events from start to the end. In addition, the indicator success of event organized by students as the EO is when they get a satisfaction testimonial from the school and coordinator of the Educational area of Merangin Regency.